The application of future studies in the military and intelligence fields - Abdelmageed, Ali Mohammed Saeed (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to highlight the reality of applying of a future study in the military and intelligence fields, where the intelligence agencies focuses on the administration of geopolitical conflicts and predict its actions and consequences, also targeting to develop means of utilizing the military force and prepare for future wars, it gives indications for staff and scholars in the intelligence domain on the significance of using the methodological and scientific means in the administration of intelligence work through the development of information centers by linking of it with future studies centers to access to timely notification and the sound decision.